A novel antimicrobial technology to enhance food safety and quality of leafy vegetables using engineered water nanostructures. Issue 2 (18th January 2021) - Huang, Runze; Vaze, Nachiket; Soorneedi, Anand; Moore, Matthew D.; Luo, Yaguang; Poverenov, Elena; Rodov, Victor; Demokritou, Philip
Abstract : Here, we report a novel, "dry", nano-aerosol-based, antimicrobial technology using engineered water nanostructures (EWNS) for leafy vegetable disinfection. Abstract : Here, we report a novel, "dry", nano-aerosol-based, antimicrobial technology using engineered water nanostructures (EWNSs) for leafy vegetable disinfection. These EWNS based nano-sanitizers are synthesized using a combined process of electrospray and ionization of aqueous solutions of generally recognized as safe active ingredients (AIs). A novel application of the EWNS to vegetable surfaces was carried out in this study. The EWNS-based nano-sanitizers were synthesized using an AI cocktail (10% hydrogen peroxide, 1% citric acid, 0.1% lysozyme and 0.0025% nisin), and their efficacy against foodborne pathogen surrogates and plant pathogens was assessed using a leafy vegetable model, namely spinach ( Spinacia oleracea) . The EWNSs were directed onto a coupon cut from spinach leaves, which were inoculated with microorganisms relevant to food safety, such as E. coli . It was shown that a 2 min exposure to EWNS-based nano-sanitizers significantly ( P < 0.05) reduced the cell populations of Escherichia coli, Listeria innocua, and Pseudomonas fluorescens on spinach by 3.5, 1.2 and 2.6 log, respectively. The EWNS also reduced Penicillium italicum spores by 1 log in 15 minutes and bacteriophage MS2 by 1.4 log in 5 minutes. More importantly, the estimated delivered dose of AIs using the EWNS approach was minuscule (258 pg cm −2 for a 15-minute exposure). No significant difference ( P > 0.05) in color or surface pH of spinach was found after 15 minutes of exposure. In summary, EWNS based nano-sanitizers are highly effective against foodborne pathogen surrogates and plant pathogens using only nanograms of nature-derived active ingredients and without an impact on produce quality.